Analisis Peluang Kejadian Deret Hari Kering Selama Musim Tanam Efektif pada Periode El Nino di Pulau Ambon - Laimeheriwa, Semuel; Amba, Martha; Putri, Nisrina Intan (Fakultas Pertanian, Universitas Pattimura, 2025)
Spell analysis is one of the indicators that can be used to measure the level of vulnerability of a region to drought. This study aims to determine the chances of a series of dry days during the effective growing season during El Niño on Ambon Island. Data analysis was carried out with the following stages: (1) calculating rainfall probability at 75% using the ranking order method and potential evapotranspiration using the Penman-Monteith method in the Cropwat 8.0 Program package, (2) calculating land water balance and determining the effective growing season based on optimum soil water content, and (3) determining the years of El Niño occurrence and the chances of a series of dry days. The results of the study showed that the effective growing season on Ambon Island lasted for 7 months, from April to October. The El Niño event on Ambon Island during the period 1979–2023 tends to occur once every three years. The chances of a series of dry days ≥ 5 days during the growing season ranged from 56 to 88%; ≥ 10 days: 27 to 88%; ≥ 15 days: 7 to 80%; and ≥ 20 days: 0 to 47%. Keywords: dry spell, growing season, El Niño, Ambon Island